Diagnostic interview study of the prevalence of depression among public employees engaged in long‐term relief work in Fukushima. Issue 9 (2nd August 2016) - Maeda, Masaharu; Ueda, Yukiko; Nagai, Masato; Fujii, Senta; Oe, Misari
Abstract : Aim: The Great East Japan Earthquake and in particular, the Fukushima Daiichi Nuclear Power Plant accident, have had a serious psychological impact on not only residents, but also relief workers in Fukushima. Although public employees work in highly stressful situations and play a very important role in long‐term relief, their psychiatric features have yet to be clarified. The two aims of this study were to identify the current prevalence rate of depression and post‐traumatic stress disorder among public employees working in the disaster area using diagnostic interviews, and to speculate on the psychosocial factors affecting their mental condition. Methods: We conducted diagnostic interviews and self‐administered questionnaires with 168 public employees working in two coastal towns in Fukushima. Results: Results showed that the current prevalence of depression among public employees is as high as 17.9%, in contrast to the relatively low prevalence of post‐traumatic stress disorder (4.8%). Based on the results of self‐administered questionnaires and interview contents, frequent exposure to strong complaints or anger from residents and role conflicts were considered the cause of the high prevalence of depression. Conclusion: The present study reveals the serious mental status of public employees working in Fukushima and sheds light on the urgent need to establish an efficient care network to provide adequate psychiatric intervention.